Hubungan Pengetahuan, Umur, Pendidikan dan Status Gizi dengan Kejadian Anemia pada Ibu hamil di RSUD La Temmamala - Hasnia Hasnia; Hajar Hajar; Inez Vravty Lestari; Herawaty Herawaty; Sumarni Sumarni; Nurhayana Nurhayana (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Pregnancy anemia is a medical condition that occurs when a pregnant woman experiences a lack of red blood cells or hemoglobin in her blood during pregnancy. Hemoglobin is a protein in red blood cells that is responsible for transporting oxygen from the lungs to the rest of the body and returning carbon dioxide to the lungs to be released. This study aims to determine the relationship between knowledge, age, education and nutritional status with the incidence of anemia in pregnant women in Soppeng district in 2024. The study design used Cross Sectional. Pregnant women at La Temmamala Hospital were 50 people. Based on the results of the Chi-square statistical test, the p Value = 0.273> α = 0.05 was obtained, so H0 was accepted and Ha was rejected, thus it can be concluded that there is no relationship between knowledge and the incidence of anemia in pregnant women at La Temmamala Hospital, Soppeng Regency. Based on the results of the Fisher's Exact Test statistical test, the p Value = 1,000 > α = 0.05 was obtained, so H0 was accepted and Ha was rejected, thus it can be concluded that there is no relationship between age and the incidence of anemia in pregnant women at La Temmamala Hospital, Soppeng Regency. Based on the results of the Fisher's Exact Test statistical test, the p Value = 1,000 > α = 0.05 was obtained, so H0 was accepted and Ha was rejected, thus it can be concluded that there is no relationship between age and the incidence of anemia in pregnant women at La Temmamala Hospital, Soppeng Regency.m Based on the results of the Chi-square statistical test, the p Value = 0.000 <α = 0.05 was obtained, so H0 was rejected and Ha was accepted. Thus, it can be concluded that there is a relationship between nutritional status and the incidence of anemia in pregnant women at La Temmamala Hospital, Soppeng Regency. For the author as information on the importance of mother's knowledge about For the author as information on the importance of mother's knowledge about the importance of ANC examination. For the government in general to optimize the dissemination of information about the importance of conducting pregnancy examinations